Developing and Testing a High-Fidelity Simulation Scenario for an Uncommon Life-Threatening Disease: Severe Malaria - Andrew Kestler; Mary Kestler; Ravi Morchi; Steven Lowenstein; Britney Anderson (Journal of Tropical Medicine)
Background. Severe malaria is prevalent globally, yet it is an uncommon disease posing a challenge to education in nonendemic countries. High-fidelity simulation (sim) may be well suited to teaching its management. Objective. To develop and evaluate a teaching tool for severe malaria, using sim. Methods. A severe malaria sim scenario was developed based on 5 learning objectives. Sim sessions, conducted at an academic center, utilized METI ECS mannequin. After sim, participants received standardized debriefing and completed a test assessing learning and a survey assessing views on sim efficacy. Results. 29 participants included 3rd year medical students (65%), 3rd year EM residents (28%), and EM nurses (7%). Participants scored average 85% on questions related to learning objectives. 93% felt that sim was effective or very effective in teaching severe malaria, and 83% rated it most effective. All respondents felt that sim increased their knowledge on malaria. Conclusion. Sim is an effective tool for teaching severe malaria in and may be superior to other modalities.